Educação escolar indígena no município de Manaus (2005-2011) - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The research addresses the course of construction of the proposed deployment of the sport indigenous education in the city of Manaus, from the historical period for the period 2005 to 2011. Conducting theoretical and methodological research was based on a qualitative approach, considering the actions of municipal government before the claims of the indigenous movement of Manaus by offering a differentiated education. The qualitative approach is endorsed by the dialectical method, showing the relationships established in the construction of differentiated school. To conduct this research, we used a literature search and document analysis. The survey shows the public policies for indigenous education, national in scope, referring to the policies outlined in the State of Amazonas in mind the education of indigenous peoples. The theoretical concepts are supported by the Cultural Diversity, Ethnic Identity, Indigenous Education and Indigenous School, which underlies the discussion of the educational process of indigenous peoples. Verifies the claims of indigenous organizations and communities to offer differentiated education according to their own learning processes of each ethnic group organized in Manaus. Identifies the actions of municipal government in meeting the demands made by indigenous peoples, considering the national guidelines for implementation of specific and differentiated school of indigenous peoples. In this process, the municipal government has made progress in setting guidelines and action plans for supply of indigenous education, however, has not achieved the implementation of this modality, it remains a challenge to be overcome by the municipal government.
Keywords: Políticas Públicas; Movimento Indígena; Educação Escolar Indígena; Public Policy; Indian Movement; Indigenous Education; CIÊNCIAS HUMANAS: EDUCAÇÃO